Pengaruh Focus Film Distance (FFD) terhadap Nilai Uji Kolimasi pada Kolimator Pesawat Sinar-X Stasioner untuk Pemeriksaan Pasien - Nathaniel Marcellino; Ni Nyoman Ratini; I Wayan Balik Sudarsana; Gusti Ngurah Sutapa; I. B. Alit Paramarta; I. G. Antha Kasmawan (Universitas Hamzanwadi, 2025)
A study has been conducted on the effect of Focus Film Distance (FFD) on the collimation test values of stationary X-ray unit collimators for patient examinations. This research aims to determine the extent to which FFD affects collimation test values. The FFD variations used were 90 cm, 95 cm, 100 cm, 105 cm, 110 cm, 115 cm, and 120 cm. There are three tests in the collimation test: illumination test, collimation field discrepancy with X-ray beam, and X-ray beam perpendicularity. The illumination test was conducted using a lux meter, which was then averaged per FFD. The resulting illumination values corresponding to the FFD variations were 425.25 lux, 381.55 lux, 343.90 lux, 311.80 lux, 283.50 lux, 259.45 lux, and 238.20 lux. These results conform to the inverse square law. For the collimation field discrepancy values |dX| and |dY|, corresponding to the FFD variations, the values were 0.68 and 0.62; 0.32 and 0.34; 0.02 and 0.02; 0.10 and 0.08; 0.18 and 0.20; 0.34 and 0.32; 0.48 and 0.50, respectively. The X-ray beam perpendicularity value remained constant for all FFD variations at 1.03º. The values obtained from the three tests comply with the Indonesian Ministry of Health Regulation No. 1250/MENKES/SK/XII/2009 concerning Quality Control Guidelines for Radiodiagnostic Equipment.